If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-2x-8=3x+1x+6-14
We move all terms to the left:
6x-2x-8-(3x+1x+6-14)=0
We add all the numbers together, and all the variables
6x-2x-(4x-8)-8=0
We add all the numbers together, and all the variables
4x-(4x-8)-8=0
We get rid of parentheses
4x-4x+8-8=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 2(x−5)=10 | | 3/4x-5/2=4 | | 4(x+2)-4=12 | | 4(3t+1)-12t+1)=0 | | 8(8−k)=−72k | | 23x^2-170x+63=0 | | -t/4=5/2 | | −2(y−3)=y+24 | | 7k+5(3-2k)=24 | | 2x=20x+10 | | 8n+10=6n+6 | | -4-v-6v=-3v-12 | | -3+x=4+2x | | x÷8.9=22 | | -6(-3x-4)=-84 | | -5+x=-3x+7 | | 3m-4=m-2 | | (2x+32/5)+(5x-4/5)=0 | | -11=7-x/ | | 4(4-x)+6x=x=16-4x | | z÷8.9=22 | | -7-3x=x+9 | | 3y+7=-6/56 | | 8x+0=26 | | 144+x^2=324 | | -2x+28=14 | | -72-13x=33-10x | | -2/3x+1/3+x=2/55 | | 7/5x=50 | | 24.5x-2+1/2=14+1/2x+17.5 | | -8+3x=4-x | | 5-10(2x+9)=45-7x |